Why has in-work poverty risen in Britain? - Pascale Bourquin; Jonathan Cribb; Tom Waters; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2019)
An increasing proportion of people towards the bottom of the UK's income distribution are in a household where someone is in paid work. Working households comprised 37% of those below the official poverty line in 1994-95 and 58% in 2017-18. Much of that increase is due to trends that seem straightforwardly positive: lower poverty rates among pensioners and workless working-age households, and less household worklessness.But about a third of the increase is due to an increase in the rate of poverty in house holds where someone works. We examine the reason for the increased in-work relative poverty rate in Britain over the last 25 years, which has risen by almost 5 percentage points to reach 18% in 2017-18. We identify two reasons why even that rise in the in-work relative poverty rate is partly a reflection of positive trends. First, the catch up of pensioner incomes (driven by higher state and private pensions) has pushed upon median income, and hence the relative poverty line. Second, falls in worklessness have brought relatively low-earning types of households (such as lone parents) into work. We show that increases in household earnings inequality among households with someone in paid work since 1994-95 explain 1.4 percentage points of the rise. The fact that housing costs have risen much more for low income households than for higher income households explains 2.4 percentage points of the rise. Working against this, increases in re-distribution towards low-income working families pushed down relative in-work poverty by 2.1 percentage points. This was due to benefit changes in the early 2000s and between 2007-08 and 2010-11 which acted to reduce relative in-work poverty, though this has been partially reversed by reductions to benefit entitlements since 2010-11.
Keywords: I32; I38; J21; J31; H53; 330; Poverty; employment; housing costs; redistribution; micro-simulation